2010
DOI: 10.3311/pp.ch.2010-2.04
|View full text |Cite
|
Sign up to set email alerts
|

Transport of NaCl, MgSO_4, MgCl_2 and Na_2SO_4 across DL type nanofiltration membrane

Abstract: The separation of inorganic ions by membrane filtration of aqueous solutions through NF-membranes was investigated. The single and binary salt solutions of NaCl, MgCl 2 , Na 2 SO 4 and MgSO 4 were used in this study. These salts are the most commonly found in natural water resources. From the research literature it was stated that NaCl has a very low rejection range with NF membranes while MgCl 2 is moderately rejected, Na 2 SO 4 and MgSO 4 are very highly rejected salts. Thus, these four salts provide a full … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The NF process can recover metallic ions, or at least retain them, and it can be used to concentrate solutions containing multivalent salts or to fractionate salts based on the different charge densities and hydrated sizes of the ions [ 22 , 23 ]. Examples of applications of ions and hardness recovery with use of NF processes are presented in many reports [ 16 , 24 , 25 , 26 ]. With the growing interest in NF as a separation technique for a wide range of applications, even under harsh conditions, ZrO 2 or TiO 2 membranes are increasingly preferred due to their high chemical, thermal and mechanical resistance [ 27 , 28 ] and easy interaction between metallic species and ceramic materials [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…The NF process can recover metallic ions, or at least retain them, and it can be used to concentrate solutions containing multivalent salts or to fractionate salts based on the different charge densities and hydrated sizes of the ions [ 22 , 23 ]. Examples of applications of ions and hardness recovery with use of NF processes are presented in many reports [ 16 , 24 , 25 , 26 ]. With the growing interest in NF as a separation technique for a wide range of applications, even under harsh conditions, ZrO 2 or TiO 2 membranes are increasingly preferred due to their high chemical, thermal and mechanical resistance [ 27 , 28 ] and easy interaction between metallic species and ceramic materials [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Enhancing the PVP ratio had a positive effect on NaCl removal efficiency as well as MgSO 4 , which provided better TFC thus NaCl removal in the membrane using 8% PVP was approximately 49%. Similarly, Ramadan et al reported that rejection of MgSO 4 salt is higher than NaCl salt because of ion transmission 50 …”
Section: Resultsmentioning
confidence: 96%
“…Bowen and co-authors [25,[43][44][45] proposed the Donnan-steric-partitioning model (DSPM) which arose from the eN-P equation. The DSPM has been also used by many authors [32,[46][47][48][49] with fairy good results. However, prediction of separation or membrane charge is very limited, and modeling is used to describe and correlate rejection results.…”
Section: Introductionmentioning
confidence: 99%